Comparing library wayfinding among novices and experts. Issue 1 (11th April 2016) - Zaugg, Holt; Child, Curtis; Bennett, Dalton; Brown, Jace; Alcaraz, Melissa; Allred, Alexander; Andrus, Nathaniel; Babcock, Drew; Barriga, Maria; Brown, Madison; Bulloch, Lindsey; Corbett, Todd; et al.
Abstract : Purpose: – The purpose of this paper is to investigate similar and different wayfinding strategies used by novice and expert patrons at an academic library. Design/methodology/approach: – The study employed a usability study approach. In total, 12 people, places, or things were identified as important for students to be able to locate within an academic library. Students from one of three groups (high school, freshmen, and seniors) were randomly assigned a scenario requiring them to find the indicated person, place, or thing. Student researchers video recorded participants and took field notes during the wayfinding activity and conducted an interview about participant's experience following the exercise. Findings: – Total and average time needed to locate the person, place, or thing indicated in the scenario were determined for each group. In addition, wayfinding tools (signs, maps, help desks, technology, and experience) used by participants were identified. Originality/value: – The research compares novice and expert wayfinding strategies. It is unique in its use of student researchers as part of a sociology class project, to collect and analyze the data.